2017
DOI: 10.1080/13540602.2017.1383237
|View full text |Cite
|
Sign up to set email alerts
|

Understanding teachers’ professional learning goals from their current professional concerns

Abstract: In the day-to-day workplace teachers direct their own learning, but little is known about what drives their decisions about what they would like to learn. These decisions are assumed to be influenced by teachers' current professional concerns. Also, teachers in different professional life phases have different reasons for engaging in professional learning. In this study, we explored the professional concerns underlying teachers' learning goals in order to understand variation in professional learning over a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 29 publications
(44 reference statements)
0
26
0
2
Order By: Relevance
“…The observation results of the teaching process to new teachers through 17 aspects of teacher performance showed good competence with an average value of 4.24 although basically, teachers, in their first years of teacher's profession, are very easily affected to learning intentionally and responsively in class (Heikonen et al, 2017). In fact, the results of the study conducted by Louws et al (2018) showed that the early career teachers had problems in growing and increasing professionalism. However, the investigated new teachers in this study showed good performance in almost all aspects assessed.…”
Section: Discussionmentioning
confidence: 97%
“…The observation results of the teaching process to new teachers through 17 aspects of teacher performance showed good competence with an average value of 4.24 although basically, teachers, in their first years of teacher's profession, are very easily affected to learning intentionally and responsively in class (Heikonen et al, 2017). In fact, the results of the study conducted by Louws et al (2018) showed that the early career teachers had problems in growing and increasing professionalism. However, the investigated new teachers in this study showed good performance in almost all aspects assessed.…”
Section: Discussionmentioning
confidence: 97%
“…Early in the project, the team identified broader impacts goals and objectives (Rule 4). Similarly, ask teachers what they want to gain from this experience and have them set their own goals [23]. Example teacher goals may include learning about emerging scientific discoveries, collaborating and/or networking with peers, acquiring new materials to teach science concepts and practices, or developing their pedagogical practice.…”
Section: Rule 8: Support Teachers To Set and Fulfill Goals For Profesmentioning
confidence: 99%
“…An average number of answers (8%) were obtained under the statement "realizing successful (inter) school projects" (o). According to Louws, Meirink, van Veen, & van Driel (2018), the teachers' concerns and professional learning goals are not constructed in vacuum but are constructed within a school context.…”
Section: Good Practices Guidelines In Nutrition Food Safety and Foodmentioning
confidence: 99%